2013
DOI: 10.1111/jdv.12243
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tanning dependence

Abstract: Background Indoor tanning has been found to be addictive. However, the most commonly-used tanning dependence measures have not been well-validated. Objective The study’s purpose was to explore the psychometric characteristics of and compare the mCAGE (modified Cut-down, Annoyed, Guilty, Eye-opener Scale), mDSM-IV-TR (modified Diagnostic and Statistical Manual of Mental Disorders – Fourth Edition - Text Revised), and TAPS (Tanning Pathology Scale) measures of tanning dependence and provide recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 42 publications
1
41
1
Order By: Relevance
“…Although HPTs are becoming increasingly popular in behavioral economic research on addictions (Bickel et al, 2011;Bickel et al, 2014;Jarmolowicz et al, 2016) and behavioral health in general , as of yet only one study has validated the TPT against two commonly used questionnaires in substance use disorder research. Given the growing number of validation studies in the substance use literature (e.g., alcohol and tobacco; Amlung et al, 2012;Amlung & MacKillop, 2014;Amlung et al, 2015;MacKillop et al, 2007;MacKillop & Lisman, 2008;MacKillop et al, 2010;Madden & Kalman, 2010), future research may attempt to validate the TPT with tanning specific addiction tools such as the Structured Interview for Tanning Abuse and Dependence (Hillhouse, Baker, Turrisi, Shields, Stapleton, Jain, & Longacre, 2012), the Tanning Pathology Scale (Heckman et al, 2014;Hillhouse et al, 2010), and experiential tasks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although HPTs are becoming increasingly popular in behavioral economic research on addictions (Bickel et al, 2011;Bickel et al, 2014;Jarmolowicz et al, 2016) and behavioral health in general , as of yet only one study has validated the TPT against two commonly used questionnaires in substance use disorder research. Given the growing number of validation studies in the substance use literature (e.g., alcohol and tobacco; Amlung et al, 2012;Amlung & MacKillop, 2014;Amlung et al, 2015;MacKillop et al, 2007;MacKillop & Lisman, 2008;MacKillop et al, 2010;Madden & Kalman, 2010), future research may attempt to validate the TPT with tanning specific addiction tools such as the Structured Interview for Tanning Abuse and Dependence (Hillhouse, Baker, Turrisi, Shields, Stapleton, Jain, & Longacre, 2012), the Tanning Pathology Scale (Heckman et al, 2014;Hillhouse et al, 2010), and experiential tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Dermatologists and other health experts surmise that much of the popularity with IT may be attributed to pleasurable consequences such as physiological sensations, 1 relaxation, perceptions of enhanced appearance, and social praise from friends and relatives (Cafri, Thompson, Roehrig, van den Berg, Jacobsen, & Stark, 2006;Day, Wilson, Hutchinson, & Roberts, 2015;Feldman et al, 2004, Heckman et al, 2014Heckman, Munshi, Darlow, Kloss, Manne, Perlis, & Oslin, 2016;Kaur et al, 2006;Stapleton, Turrisi, Hillhouse, Robinson, & Abar, 2010). To our knowledge, no studies have examined the cue-induced effects on craving and demand for IT.…”
mentioning
confidence: 88%
“…84 The overall prevalence of tanning dependence differs by population and method of measurement with the highest rates seen in college-aged indoor tanners (22%-45%). 85 …”
Section: Phototypementioning
confidence: 97%
“…53 In addition to the desire for a tanned appearance, a growing number of studies are uncovering tanning addiction or dependence as a potential driver of this behavior. [54][55][56][57] 61 A US survey found that most salons would allow minors to tan twice the number of times recommended by the US Food and Drug Administration. 63 To prevent skin cancers, in 2012 the US Preventive Services Task Force recommended that children, adolescents, and young adults (10-24 years) with fair skin be counseled to minimize UV radiation exposure, including from indoor tanning (a Grade B recommendation).…”
Section: Discussionmentioning
confidence: 99%